FERTILITAS MENURUT ETNIS DI INDONESIA: ANALISIS DATA SENSUS PENDUDUK 2010 - Mugia Bayu Raharja (Research Centre for Population, Indonesian Institute of Sciences, 2017)
Indonesia is known as a country that has the largest ethnic groups in the world with 1,128 ethnic groups as reported on the 2010 Population Census. Ethnic diversity is one of the important factors that determine the amount and distribution of the population in Indonesia. This study aimed to determine variations and patterns of fertility by ethnic groups in Indonesia and its association with their socioeconomic characteristics. By using the 2010 Population Census raw data that obtained from the IPUMS website, this study calculated the average number of children born alive born to ever married women aged 15-49. The results show a relationship between fertility and ethnic groups. Among fifteen major ethnic groups analyzed in this study, Batak ethnic has the highest fertility rate followed by Acehnese and Bantenese, while ever married Maduranese women have the lowest fertility rate. The high level of fertility in some of the major ethnic groups in Indonesia is associated with the desire to have many children, the low age at first marriage of women, and the existed perception that those with many children would get higher social value. Low level of education and rural residential areas also contribute to high fertility rates.